A demonstration area for type 2 diabetes prevention in Barranquilla and Juan Mina (Colombia): Baseline characteristics of the study participants. Issue 1 (January 2018) - Acosta, Tania; Barengo, Noël C.; Arrieta, Astrid; Ricaurte, Carlos; Tuomilehto, Jaakko O.
Abstract : Abstract: Type 2 diabetes (T2D) imposes a heavy public health burden in both developed and developing countries. It is necessary to understand the effect of T2D in different settings and population groups. This report aimed to present baseline characteristics of study participants in the demonstration area for the "Type 2 Diabetes Prevention in Barranquilla and Juan Mina" (DEMOJUAN) project after randomization and to compare their fasting and 2-hour glucose levels according to lifestyle and T2D risk factor levels. The DEMOJUAN project is a randomized controlled field trial. Study participants were recruited from study sites using population-wide screening using the Finnish Diabetes Risk Score (FINDRISC) questionnaire. All volunteers with FINDRISC of ≥13 points were invited to undergo an oral glucose tolerance test (OGTT). Participant inclusion criteria for the upcoming field trial were either FINDRISC of ≥13 points and 2-hour post-challenge glucose level of 7.0 to 11.0 mmol/L or FINDRISC of ≥13 points and fasting plasma glucose level of 6.1 to 6.9 mmol/L. Lifestyle habits and risk factors for T2D were assessed by trained interviewers using a validated questionnaire. Among the 14, 193 participants who completed the FINDRISC questionnaire, 35% (n = 4915) had a FINDRISC score of ≥13 points and 47% (n = 2306) agreed to undergo the OGTT. Approximately, 33% (n = 772) of participants underwent the OGTT and met the entry criteria; these participants were randomized into 3 groups. There were no statistically significant differences found in anthropometric or lifestyle risk factors, distribution of the glucose metabolism categories, or other diabetes risk factors between the 3 groups ( P  > .05). Women with a past history of hyperglycaemia had significantly higher fasting glucose levels than those without previous hyperglycaemia (103 vs 99 mg/dL; P  < .05). Lifestyle habits and risk factors were evenly distributed among the 3 study groups. No differences were found in fasting or 2-hour glucose levels among different lifestyle or risk factor categories with the exception of body mass index, past history of hyperglycaemia, and age of ≥64 years in women. Trial registration: NCT01296100 (2/12/2011; Clinical trials.gov).